Pengaruh prenatal yoga terhadap ketidaknyamanan pada ibu hamil trimester III - Yuniza Yuniza; Marwan Riki Ginanjar (STIKes Surya Global Yogyakarta, 2021)
Pregnancy is a series of events that occur when an egg cell meets a sperm cell and will develop into a mature fetus. In the event of pregnancy, physical and psychological changes occur, from physical changes will result discomfort which will have a negative impact on the fetus and pregnant women. This study purposes to determine the effect of prenatal yoga on discomfort in third trimester pregnant women. This type of research was conducted in the form of quasy experiment using pre and posttest one group design with a total sample of 35 respondents. Data collection using questionnaire instruments and interviews. This study used the Shapiro wilk normality test, univariate test and bivariate test. This research show that There was an effect of prenatal yoga on discomfort in third trimester pregnant women seen from the p-value = 0,000 0,05. There is an effect of Prenatal Yoga practice on discomfort in third trimester pregnant women.